Stover quality and soil organic carbon in long-term nitrogen-fertilized maize - Melchiori, Ricardo J. M. (2014)
Nitrogen fertilization often increases maize (Zea mays L.) grain yield but reduces the C/N ratio of stover returned to the soil, which may affect the soil organic carbon (SOC) balance. This study evaluated the long-term effect of N fertilization on maize grain yield, stover quality in terms of its C/N ratio, and its effect on SOC. In addition, a simulation approach was used to account for the effect of stover quality on its mineralization and SOC balance. Maize grain yield, stover production and quality, and SOC stock were measured during a 6-yr period (2006–2012) in a long-term N fertilization experiment under continuous maize since 1994 in Paraná, Argentina. On average, grain yield ranged from 5.06 in 2011 to 9.10 Mg ha–1in 2009. The N effect on grain yield, significant in all seasons, was more important than the effect on C stover production. In contrast, stover C/N ratio showed a linear decrease as a function of N fertilization. Changes in the stover C/N ratio were inversely proportional to the difference between the N rate and the agronomical optimum nitrogen rate (AONR). Although N fertilization increased stover C inputs in 3 out of 6 yr, SOC stock remained unchanged. Simulation results indicate that the required stover amount to maintain the SOC stock increased as the C/N ratio decreased. Our results contribute to better understanding of the previous, controversial results of the N effect on SOC and provide useful insights to develop or improve simulation models for SOC dynamics.